Learning Thermal Expansion with Unity: An Interactive Simulation - Soto, Dewin A.; Vesga, Carlos A.; Racedo, Francisco J.; Valbuena, Sonia (Journal of Posthumanism, 2025)
The use of Unity and Virtual Reality in education facilitates active exploration, safe experimentation, and personalized learning, enhancing knowledge retention. Their integration transforms traditional teaching by providing innovative and immersive experiences that allow users to understand the concepts of science easily. In this context, an interactive simulation was developed using the Unity 3D graphics engine and the C# programming language to study the phenomenon of thermal expansion, addressing the complexity of solid materials’ behavior under temperature changes. The model’s accuracy was evaluated through numerical validation, comparing the simulated results with theoretical values. The simulation showed a close correlation with expected values, with an error margin of less than 1%, confirming its high fidelity in representing thermal expansion. It is concluded that the use of Unity and VR significantly contributes to understanding key concepts in thermal physics, offering an effective and visually engaging alternative for educational laboratories.